Literature Review of Lean Six Sigma (LSS) Implementation and Recommendations for Implementation in the Defense Industries - Sarman, Sarman; Soediantono, Dwi (Journal of Industrial Engineering & Management Research, 2022)
Lean six sigma (LSS) has been widely used in various industries to improve performance and competitiveness. The purpose of this article is to explore the benefits of implementing lean manufacturing in various industries and provide recommendations for application to the defense industry. The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 35 international journal articles published from 2010 to 2021 regarding the application of the six sigma method in various industrial sectors and the defense industry. The analysis used used 25 content analyzes of journal articles, which had been collected and then looked for similarities and differences and then discussed to draw conclusions. The results of the literature review analysis state that the application of the LSS method can reduce variation, measure defects and improve product, process and service quality, reduce cycle time and eliminate waste in the process. resulting in reduced delivery duration, lower costs, and increased customer satisfaction. LSS increases customer satisfaction, cost, quality, process speed, and invested capital. eliminate waste and reduce defects and variations in organizational processes. The application of LSS can be recommended to be applied in the defense industry.